Fuzzy Systems & Operations Research and Management - Cao, Bing-Yuan.; Liu, Zeng-Liang.; Zhong, Yu-Bin.; Mi, Hong-Hai.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book includes results of the seventh International Conference on Fuzzy Information and Engineering (ICFIE'2014) and the 1st International Conference of Operations Research and Management (ICORM'2014) on November 7-11, 2014 in ZhuHai, China. The book, contains 35 selected high-quality papers, and is divided into five main parts: Part I focuses on ``Fuzzy Systems and Its Applications", Part II on ``Fuzzy Mathematics and Its Applications", Part III discusses ``Fuzzy Information and Computer", Part IV is devoted to ``Operations Research and Management and Its Applications" and Part V includes various other topics.  .
Part I Fuzzy Systems and Its Applications -- Part II Fuzzy Mathematics and Its Applications -- Part III Fuzzy Information and Computer -- Part IV Operations Research and Management and Its Applications -- Part V Others.
Keywords: Computational intelligence; Artificial intelligence; Operations research; Computational Intelligence; Artificial Intelligence; Operations Research and Decision Theory